The Use of Cake Application to Improve Students’ Speaking Skills at Kwala Madu Boarding School - Khairun Niswa; Ambar Wulan Sari; Habib Syukri Nasution (English Teaching and Linguistics Journal (ETLiJ), 2026)
This study aims to investigate the use of the Cake application in improving students’ speaking skills at Kwala Madu Boarding School, given that many students face difficulties in expressing their ideas due to limited vocabulary, lack of confidence, and minimal practice opportunities. A quantitative approach with a pre-experimental one-group pre-test–post-test design was employed, involving students at Kwala Madu Boarding School selected through purposive sampling. Data were collected through speaking tests, observation, and documentation; students completed a pre-test prior to the implementation of the Cake application and a post-test after several treatment sessions. The results show that students’ speaking skills improved significantly from pre-test (M = 52.45, SD = 9.86) to post-test (M = 77.38, SD = 7.46), t(28) = 49.04, p .001, d = 9.11, with students becoming more confident, active, and motivated in speaking English. The application’s interactive features, such as video-based learning and pronunciation practice, contributed to gains in fluency and accuracy. It is concluded that the Cake application is an effective tool for enhancing students’ speaking skills and can be recommended as an alternative learning medium in English language teaching, particularly in boarding school contexts.